2007
DOI: 10.1007/s11255-007-9318-3
|View full text |Cite
|
Sign up to set email alerts
|

Do microdeletions in the AZF region of the Y chromosome accompany cryptorchidism in Turkish children?

Abstract: Studies on Y chromosome microdeletions are important due to a potential for the transmission of genetic abnormalities to offspring. Assisted reproduction techniques may cause the transmission of genetic abnormalities to offspring because the physiological fertilisation mechanism is bypassed. It was found that there was probably no aetiologic correlation between microdeletions in gene loci on the AZF-a, AZF-b and AZF-c regions of the Y chromosome and cryptorchidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…Similar varying results have been reported in studies of trinucleotide repeat number in exon 1 of the androgen receptor, although more recent work suggests a possible association with cryptorchidism [20]. Microdeletions of the Y chromosome have also been studied in infertile men with and without a history of cryptorchidism, and no consistent association observed (reviewed in [30]). …”
Section: Candidate Gene Mutations In Human Cryptorchidismsupporting
confidence: 55%
“…Similar varying results have been reported in studies of trinucleotide repeat number in exon 1 of the androgen receptor, although more recent work suggests a possible association with cryptorchidism [20]. Microdeletions of the Y chromosome have also been studied in infertile men with and without a history of cryptorchidism, and no consistent association observed (reviewed in [30]). …”
Section: Candidate Gene Mutations In Human Cryptorchidismsupporting
confidence: 55%
“…A few studies have focused on Υq11-md specifically in patients with TMD (Cortes et al, 1998;Fagerli et al, 1999;Foresta et al, 1999;Dada et al, 2002b;Suzuki et al, 2002;Kunej et al, 2003;Castro et al, 2004;Ferlin et al, 2004Ferlin et al, , 2005Song et al, 2005;Bor et al, 2006;Giachini et al, 2007;Moretti et al, 2007;Gurbuz et al, 2008). To our knowledge, our study is the largest one published to date (Table 1).…”
Section: Discussionmentioning
confidence: 76%
“…However, it should be noted that this study is not directly comparable to ours in terms of the STS primers used. Finally, Gurbuz et al (2008) in a study of 64 Turkish patients with TMD (and unknown fertility status) no Yq11-md were found. All three AZF regions were screened with the use of 51 STS primers, including those used in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The LHCGR has been excluded as a CO candidate gene in an association study in men [71], although KO of this gene in mice showed cryptorchid phenotype (MGI) and is causative gene of Leydig cell hypoplasia-a syndrome that features CO as one of the clinical signs (OMIM). In addition, Y chromosome microdeletions have been found to be present in patients with CO, but are not likely to be a common etiological cause of CO [72-74]. …”
Section: Resultsmentioning
confidence: 99%